An Overview of the Effects and the Discussion of Sirah in the Sermons of Hazrat Imam Hassan (RA): حضرت امام حسن رضی اللہ تعالیٰ عنہ کے خطبات میں مباحثِ سیرت ا و ران کےاثرات کا جائزہ - Munawar, Hifsa; Najam Barvi, Dr. Muhammad Ramzan (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
A lot of people have been mentioned in Quran and Allah Almighty has blessed them with the ability of Oration .The Quran has addressed such men as "the men of strength " and "men of vision ".These "men of vision " are known as Khulfa –e-Rashdeen. Hazrat Imam Hassan (RA) is the one to complete the series of Khulfa-e-Rashdeen.Like the Khulfa-e-Rashdeen Hazrat Imam Hassan (RA) guided the people through his sermons. These sermons contain guidance for self analysis. His sermons are a beacon and a ray of guidance for every individual of the human race. His sermons are a collection of discourses that were required by the circumstances but at the same time are a great and valuable treasure of Seerat-e-Taiba (SAW) discourses. The essence of his speech impressed many people. That is why the desired result of his speech came to light very soon. People accepted its effect and a reformed society was established. In this time, the study of sermons of Imam Hassan (RA) is also important because through these sermons the message of Prophet (SAW) may conveyed get to the people and a peaceful society may be established.